Competency-Based Laboratory Manual:A Study - Earnest, Joshua; Kerkal, S. R. (Journal of Engineering Education Transformations, 1999)
This paper is condensed from the dissertation of S. R. Kerkal, and written by both he and his guide Prof .. Joshua Earnest, which was accepted by the Barkatullah University, Bhopal, M. P. , (India) towards the partial-fulfillment for the award of the Masters in Technical Education, 1997. It highlights the experience lfl developing a 'Competency-Based Laboratory Manual in Hydraulics'. for this, the competencies required ill the area of hydraulics were identified from the working professionals and the laboratory manual was designed, developed and tried out all the sample of students. The competency maps ill the dissertation were developed in partnership with the working professional. The results of this experiment and the main features of the competency-based; laboratory manual are highlighted in this paper; which could serve as 'starter' to develop laboratory manuals in other areas.